Basic Features of Structural Equation Modeling and Path Analysis with Its Place and Importance in Educational Research Methodology - E. Karadag (University of Sofia, 2012)
It has recently been seen that structural equation modeling and especially path analysis have been started to be used frequently in the field of social sciences. However, when educational research is examined, particularly, it can be said that these instruments are not used so much in this field in comparison with the other social sciences fields. Therefore, structural equation modeling and, among its mostly used analysis tests, path analysis are needed to be utilized in educational researches and become widespread. For this purpose, the basic features of structral equation modeling and path analysis with their use and importance in educational sciences have been discussed in this study. Firstly, these two are analysed and their features are outlined. Then the matter why they should be used in the resarch on education has been explained with proper examples.